IMPLEMENTASI TUJUH KEBIASAAN ANAK INDONESIA HEBAT TERHADAP PEMBENTUKAN KARAKTER RELIGIUS PESERTA DIDIK DI SD NEGERI KENDAWA 02 - Ica Amalia; Farhan Saefudin Wahid; Atikah Mumpuni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research uses a descriptive qualitative approach aimed at analyzing the influence of the seven habits of great Indonesian children on the character of students in everyday life. In addition to using data collection techniques with triangulation (combination), the analysis is inductive or qualitative. The results obtained from using qualitative research itself emphasize the meaning of generalizations. Based on the research results, conducted through interviews and observations, it was found that the implementation of the Seven Habits of Great Indonesian Children at SD Negeri Kendawa 02 has a significant influence on the formation of student character in everyday life. Habits such as waking up early, maintaining health, being grateful, and being active in the learning process have been successfully internalized in student behavior, which is reflected in the improvement of their responsibility, independence, creativity, and academic and social abilities.